Inmates Of Narcotics Cases And Diversity Development In Correctional Institutions - Kurniawan, Andi; Faiz Fakhri Isjwara (PT. Anagata Sembagi Education, 2025)
Personality coaching is coaching whose focus is on emphasizing the development of attitudes and personality. Personality development aims to help prisoners to recognize and develop themselves according to a healthy and correct life. Personality development is realized in forms such as fostering awareness in religion, fostering awareness of nation and state, intellectual development, and fostering legal awareness. This research uses descriptive qualitative research methods, because the description is described in the form of qualitative data such as interviews. Sources of data collection information from interviews, observations and documents. This research focuses on narcotics case inmates. The results of this study regarding the coaching that is realized in the form of personality coaching and independence coaching programs. The initial door for the prisoner to return to the community / social reintegration by strengthening the personality development program and then implementing an independence program to support the prisoner after returning to the community